Identifying proteomic risk factors for cancer using prospective and exome analyses of 1463 circulating proteins and risk of 19 cancers in the UK Biobank - Papier, Keren; Atkins, Joshua R.; Tong, Tammy Y. N.; Gaitskell, Kezia; Desai, Trishna; Ogamba, Chibuzor F.; Parsaeian, Mahboubeh; Reeves, Gillian K.; Mills, Ian G.; Key, Tim J.; Smith-Byrne, Karl; Travis, Ruth C. (Nature communications, 2024)
The availability of protein measurements and whole exome sequence data in the UK Biobank enables investigation of potential observational and genetic protein-cancer risk associations. We investigated associations of 1463 plasma proteins with incidence of 19 cancers and 9 cancer subsites in UK Biobank participants (average 12 years follow-up). Emerging protein-cancer associations were further explored using two genetic approaches, cis -pQTL and exome-wide protein genetic scores (exGS). We identify 618 protein-cancer associations, of which 107 persist for cases diagnosed more than seven years after blood draw, 29 of 618 were associated in genetic analyses, and four had support from long time-to-diagnosis ( > 7 years) and both cis -pQTL and exGS analyses: CD74 and TNFRSF1B with NHL, ADAM8 with leukemia, and SFTPA2 with lung cancer. We present multiple blood protein-cancer risk associations, including many detectable more than seven years before cancer diagnosis and that had concordant evidence from genetic analyses, suggesting a possible role in cancer development. Plasma proteins are a potential diagnostic tool to detect multiple diseases, including cancer. Here, the authors leverage multi-omics data to identify 1,463 proteins associated with 19 common cancers in UK Biobank participants. Reviewer Recognition: